2010
DOI: 10.1177/0267659110382686
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with pericardial suction blood and residual pump volume: a review of current practices in the UK

Abstract: The pathological effects of pericardial suction blood (PSB) have been well described in numerous studies for many years; yet, despite this, there is no definitive answer to the question of how best to attenuate this pathology. More recently, large studies have shown that, whilst PSB contains many factors indicating its pathological potential, the direct re-infusion of PSB and residual pump volume (RPV) after cardiopulmonary bypass (CPB) potentially reduces the risk of transfusion and is no more harmful to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…The infusion bag is retransfused either as it is or washed in a cellsaver 23 . It has been shown that when the blood is washed in a cellsaver the quality is improved 10,24,25 because heparin, inflammatory mediators and by-products from coagulation and fibrinolysis are removed.…”
Section: Retransfusion Techniquesmentioning
confidence: 99%
See 4 more Smart Citations
“…The infusion bag is retransfused either as it is or washed in a cellsaver 23 . It has been shown that when the blood is washed in a cellsaver the quality is improved 10,24,25 because heparin, inflammatory mediators and by-products from coagulation and fibrinolysis are removed.…”
Section: Retransfusion Techniquesmentioning
confidence: 99%
“…The residual pump blood is retransfused after weaning from CPB 23 in order to reduce the need for allogenic blood transfusion. The most common technique is to retransfuse the blood by the IB technique, but the RC technique is also used.…”
Section: Hypothesismentioning
confidence: 99%
See 3 more Smart Citations